DAMPAK SATPAM DALAM PENCIPTAAN DISIPLIN BAGI SISWA SD AL-MADINA WONOSOBO TAHUN Ajaran 2022/2023 - maulida, hanim; Jumini, Sri; Sugiyanto, Bambang (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2023)
The process of instilling student discipline values at SD Al-Madina Wonosobo is very important so that students can excel and teachers can show their best performance. teachers and SATPAM to instill discipline in SD Al-Madinah students, namely contextual learning, external control and internal control, namely the teacher or SATPAM provides a living example and controls students to follow discipline and get to know students so they realize the importance of discipline. In the data collection process, the authors used qualitative research by means of observation, interviews and arithmetic as data collection techniques.